Therapeutic advantages of omega-3 fatty acid supplementation in patients with schizophrenia – a systematic review - Vityala, Srilaxmi; Kanteti, Krishna Priya; Vityala, Yethindra; Tagaev, Tugolbai; Damineni, Ujwala (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. In patients with schizophrenia, omega-3 (n-3) polyunsaturated fatty acids (PUFAs) treatment was found to ameliorate the cardiovascular, metabolic, and inflammatory problems caused by antipsychotic medication and even reduce the need for medication by 20%. In this study, we evaluated the potential therapeutic effects of n-3 PUFA supplementation in patients with schizophrenia. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The PRISMA guidelines were followed in conducting this systematic review. The Embase, MEDLINE, Web of Science, and Google Scholar databases were searched electronically. The first search yielded 50 papers in total. Subse quently, 43 publications that did not meet our eligibility requirements were removed, and seven articles were selected. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of the literature. The analysis showed that n-3 PUFA supplementation and the placebo group both decreased their psychotic (PANSS and GAF scales) and Calgary Depression Scale symptomatology and boosted their functional ability (GAF) when used as an adjuvant to antipsychotic medication. When administered as a monotherapy with a metabolic antioxidant, n-3 PUFA supplementation proved beneficial for treating schizophrenia. In patients with schizophrenia, n-3 PUFAs have thera peutic benefits as adjuvant treatments to medications, although not for different variables or patient groups. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. In many studies, patients with chronic schizophrenia who received n-3 PUFA supplementation showed no improvement in their clinical condition.